1991
DOI: 10.1056/nejm199110173251602
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Intraarticular Morphine after Arthroscopic Knee Surgery

Abstract: Low doses of intraarticular morphine can significantly reduce pain after knee surgery through an action specific to local opioid receptors that reaches its maximal effect three to six hours after injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
169
2
13

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(195 citation statements)
references
References 11 publications
11
169
2
13
Order By: Relevance
“…According to recommendations given by Stein et al, 19 we gave morphine intra-articularly at a dose of 1 mg and found a similar effect. A morphine infusion given into the joint during arthrocentesis substantially decreases pain and this could be useful at the rate of 90%.…”
Section: Discussionmentioning
confidence: 58%
“…According to recommendations given by Stein et al, 19 we gave morphine intra-articularly at a dose of 1 mg and found a similar effect. A morphine infusion given into the joint during arthrocentesis substantially decreases pain and this could be useful at the rate of 90%.…”
Section: Discussionmentioning
confidence: 58%
“…analgesic effect was abolished by the opioid antagonist naloxone. These findings indicate that peripheral opioid receptors can mediate analgesia (Stein, 1991). Are there cytokines other than TNF-a, lL-1 P. and IL-6 or factors other than CRF which affect peripheral opioid analgesia?…”
Section: Ruman Studies Of Peripheral Opioid Analgesiamentioning
confidence: 97%
“…Obviously, analgesia in humans is the ultimate goal of pain research and several studies using surgery patients have been performed by Christoph Stein (1991). His findings, summarized below, justifY further investigations into this field .…”
Section: Ruman Studies Of Peripheral Opioid Analgesiamentioning
confidence: 99%
“…In den 1980er Jah ren wur de der pe ri phe ren Opioidanalge sie wie der ver mehrt Auf merk sam keit geschenkt und die ge won ne nen ex pe ri mentel len Er geb nis se konn ten 1991 in der ersten kon trol lier ten kli ni schen Stu die zur pe ri phe ren Opioidanal ge sie bei in tra ar tiku lä rer Ap pli ka ti on von Mor phin nach arthro sko pi schen Ein grif fen am Knie ge lenk ins Hu man mo dell über tra gen wer den [70,71]. Seit her ist der Zu wachs an ex pe ri mentel len und kli ni schen Da ten durch die zuneh men de An zahl an Stu di en, die das Kon zept der Schmerz kon trol le durch die pe ri phe re Ap pli ka ti on von Opioiden [68] ver deut li chen, groß.…”
unclassified